Utilization of Ornamental Plants as Phytoremediation Agents to Reduce Lead (Pb) Contamination in Urban Area - Laela, Fadhilatul; Ammurabi, Syah Deva (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Laela, F., & Ammurabi, S.D. (2024). Utilization of Ornamental Plants as Phytoremediation Agents to Reduce Lead (Pb) Contamination in Urban Area. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 48–58). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Lead (Pb) is one of common heavy metal pollutant that produced from human activities. Lead pollution produced from fuel, mining activities, fertilizer, pesticides application, and industrial activities that contribute to urban pollution level. Lead concentration in soil cause health problems such as digestive disorders, kidney disease, anemia, and decrease of intelligent quotient (IQ) score. High concentration of blood lead level caused negative health impacts such as increase of cardiovascular diseases, kidney failure, blood anemia, loss of vision, and bones impair development. Recent science development has given us several alternatives to reduce lead contamination in water and soil, one of which is phytoremediation. Phytoremediation is a process of soil and water decontamination from hazardous substances with plants. Ornamental plants become alternative method of lead phytoremediation because it is unconsumed by human and animals as well as served decorative function. In this paper, various ornamental plant species that show a high capacity to tolerate, accumulate, and improve contaminated soil of lead will be described. Plants with lead phytoremediaton abilities could become solution for urban green space utilization in Indonesia. The purpose of this paper was to determine the types of ornamental plants that can be used as phytoremediators for lead (Pb) contamination in urban areas and to determine the mechanism process.